1988
DOI: 10.1111/j.1467-1770.1988.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Second‐Language Accent: The Relationship Between Discrimination and Perception in Acquisition*

Abstract: This paper reports on a study which measures the relationship between the discrimination and production of segmental and prosodic elements in a second language. The measures employed in the study also served to assess the effects of a phonetic training program for French as a second language designed by the authors. Two questions are addressed in the present study: 1) Is there a systematic relationship between perception and production of the sound system in a second language? 2) What effect does a period of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Problems in the acquisition of pronunciation have provided the main arguments to support the critical age hypothesis (Singleton 1989), as it has been observed that most adult learners of a second language retain a foreign accent (Flege 1987;Major 1987a). Nevertheless, it has been argued that adults have the same ability as children to discriminate speech sounds (Schneiderman, Bourdages & Champagne 1988), but they perceive new sounds in terms of the categories of their first language (Best 1994;Polka 1995). It has also been suggested that age is not necessarily a causal factor in the acquisition of pronunciation and that motivation and identity are also influential (Major 1987a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems in the acquisition of pronunciation have provided the main arguments to support the critical age hypothesis (Singleton 1989), as it has been observed that most adult learners of a second language retain a foreign accent (Flege 1987;Major 1987a). Nevertheless, it has been argued that adults have the same ability as children to discriminate speech sounds (Schneiderman, Bourdages & Champagne 1988), but they perceive new sounds in terms of the categories of their first language (Best 1994;Polka 1995). It has also been suggested that age is not necessarily a causal factor in the acquisition of pronunciation and that motivation and identity are also influential (Major 1987a).…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of a second language phonetic component is a complex and dynamic process which is affected by the context and the conditions in which the second language is being learnt. Aptitude, affective and social factors have been pointed out as possible predictors of second language phonetic performance (Flege 1987;Schneiderman et al 1988). The ability to mimic has been reported to exert a significant influence on second language pronunciation (Suter 1976;Purcell & Suter 1980;Thompson 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Discrimination tasks are also incorporated into some production exercises. The focus on discrimination prior to production is based on an earlier study in which improvement in discrimination ability was shown to lead to improved production (Schneiderman, Bourdages and Champagne, 1988). Appendix A contains a catalogue of the phonetic elements and exercise types included in the phonetic training program.…”
Section: The € Training Programmentioning
confidence: 99%
“…As Lowenberg (1986) Visual cues such as appearance and body language could also be investigated using videotaped speech samples, and studies involving perception could be conducted to determine i f "nativeness of accent would vary as a function of one's ability to perceive segmental and supraseginental aspects of that language" (Schneiderman, Bourdages and Champagne, 1988 In this section, you will be asked to read a printed paragraph aloud. First, you will be given one mihute to read the paragraph silently to yourself.…”
Section: Discussionmentioning
confidence: 99%